El papel de la vestimenta en los rituales mexicas de “personificación” - Danièle Dehouve (Nuevo mundo - Mundos Nuevos, 2016)
During their ceremonies, the Mexica or Aztecs of central Mexico used certain costumes woven with cotton or vegetable fibres, or simply made of amate paper, covered with designs. This article seeks to explain the variety of these ritual garments utilizing a native concept of "personification" (ixiptla in nahuatl), in which a support (the "impersonator") is covered with a garment and various adornments belonging to a god (the "personified"), in order to transform it into the god’s divine incarnation.